The Role of the Police in Providing Legal Protection for Child Victims of Indecent Acts (Case Study of Natuna Regency) - Sinambela, Stheven Nerea; Winjaya Laksana, Andri (UNISSULA Semarang, 2025)
Abstract. Protection of the life and livelihood of children is still the responsibility of various parties, namely both parents, their families, society, and also the state. This protection can be in the form of clothing, food, and shelter. Not only that, the protection given to a child can also be in the form of protection against the psychological or mental condition of the child, especially their mental development. This means that the child can develop and live normally, not only in terms of physical development but also in terms of mental or psychological development. Furthermore, protection against the form of protection is legal protection against victims of criminal acts, which can be interpreted as protection to obtain legal guarantees for the suffering or loss of the party who has become a victim of a criminal act. Philosophically, children are the future of the nation, and as the next generation of the struggle, a child who has problems means becoming a problem for the nation, therefore the best interests of the child are the interests that must be prioritized in dealing with children who have problems or who are in conflict with the law. Children must be protected so that they do not become victims of anyone's actions (individuals or groups, private or government organizations) either directly or indirectly. Victims are those who suffer losses (mental, physical, social), due to passive actions, or active actions of other people or groups (private or government), either directly or indirectly. The crime of indecent assault is not only regulated in the Criminal Code but also regulated in Law No. 23 of 2002 concerning Child Protection. The Criminal Code states that indecent assault is contained in Article 289 of the Criminal Code which states that: